Assessing the financial viability of the floricultural industry in Ghana - Donkor, Emmanuel; Owusu-Sekyere, Enoch; Owusu, Victor; Saadu, Samira; Baidoo, Jacqueline; Yaw, Hennor Avame; Kwesi, Djamson Eric; Serbeh, Felix Owusu (Applied Studies in Agribusiness and Commerce, 2017)
This study determines the financial viability of the floricultural industry in Ghana using both discounting and non-discounting investment appraisal methods. The feasibility analysis suggests that large-scale floricultural firms are more profitable particularly with the production of cut flowers. However, investors with limited capital can venture into small-scale production specifically cut flowers. The conclusion is that the floriculture industry is financially viable therefore investors are encouraged to expend their resources in the industry. We recommend that the government and stakeholders need to create institutional support to enable the already established firms to further develop and attract new investors in the sector.JEL. Code: Q13